STUDI BUDAYA BATAK (Studi Kasus Budaya Batak Melalui Wisata di Tugu Siraja Nabarat, Tugu Manurung, Tugu Siagian, Tugu Sonakmalela, Makam Dr. IL. Nomensen dan Sisimangaradja XII) - Yerniman Gulo; Merry Moy Mita (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
This study reveals how the relationship between the establishment of the monument and the traditional belief system of the Toba Batak people who still believe in the existence of the spirits of their ancestors. The actualization of this belief is manifested in the construction of an ancestral monument which is considered an embodiment of respect for the descendants of the clan that founded it. To reveal these data, in this study the authors used qualitative research. The data in the field were obtained through participatory observation techniques, interviews, and literature studies. The purpose of this study was to reveal the background of the establishment of monuments in clan groups in Balige District, Toba Samosir Regency which represents the function and meaning of the erection of clan monuments in Balige District. Toba Samosir Regency also describes the organization and implementation of the case for the establishment of the Siraja Nababat, Manurung, Nommensen, Siagian, Sonakmalela and Sisimangaraja XII monuments in and analyzes the conception of the construction of the monument in the Toba Batak community. based on the conception of traditional beliefs that believe in the existence of their ancestral spirits in people's lives. The worship of ancestral spirits is manifested in the construction of monuments. This research was conducted in the Tourism Area in the City of Balige and Porsea – North Sumatra. The aims of this study include: (1) As a deeper learning material about the reasons why Batak Culture built the Tugu, and (2) To explore and promote the richness of culture, tradition, history in the Batak tribe. The results showed that (1) all visitors who came were very enthusiastic about the history of the construction of each existing monument, (2) the role of both local and foreign tourists had a positive impact on the community, namely the development of local community knowledge systems, the emergence of new livelihoods, getting to know language diversity, technological progress, the formation of social organizations, the emergence of the commercialization of hospitality, the shift in the value of solidarity in agriculture. Cultural tourism is a travel activity carried out by certain parties (a person or group of people) by visiting certain places with the aim of learning about cultural attractions or taking advantage of the cultural potential of the places visited.